Magnetic resonance imaging suggests functional role of previous year vessels and fibres in ring-porous sap flow resumption. (28th March 2019) - Copini, Paul; Vergeldt, Frank J; Fonti, Patrick; Sass-Klaassen, Ute; den Ouden, Jan; Sterck, Frank; Decuyper, Mathieu; Gerkema, Edo; Windt, Carel W; Van As, Henk
Abstract: Reactivation of axial water flow in ring-porous species is a complex process related to stem water content and developmental stage of both earlywood-vessel and leaf formation. Yet empirical evidence with non-destructive methods on the dynamics of water flow resumption in relation to these mechanisms is lacking. Here we combined in vivo magnetic resonance imaging and wood-anatomical observations to monitor the dynamic changes in stem water content and flow during spring reactivation in 4-year-old pedunculate oaks ( Quercus robur L.) saplings. We found that previous year latewood vessels and current year developing earlywood vessels form a functional unit for water flow during growth resumption. During spring reactivation, water flow shifted from latewood towards the new earlywood, paralleling the formation of earlywood vessels and leaves. At leaves' full expansion, volumetric water content of previous rings drastically decreased due to the near-absence of water in fibre tissue. We conclude (i) that in ring-porous oak, latewood vessels play an important hydraulic role for bridging the transition between old and new water-conducting vessels and (ii) that fibre and parenchyma provides a place for water storage.